The Construction of Masculinity in Relation to Vasectomy Practices in Indonesia’s Family Planning Program - Olivia, Melisa; Nugroho, Farhan Bintang; Indriyany, Ika Arinia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Family Planning (KB) program in Indonesia still demonstrates unequal participation between women and men, particularly in the use of permanent contraceptive methods such as vasectomy. This study aims to analyze the causes of low male involvement and examine the influence of masculinity construction on reproductive decision-making. The research employs a qualitative method using a literature review approach. The findings indicate that low male participation is influenced by strong patriarchal values, the perception of fertility as a symbol of masculinity, as well as limited knowledge and access to reproductive health services. From the perspective of hegemonic masculinity, vasectomy is often perceived as a threat to masculine identity, leading to social resistance. Consequently, the responsibility for contraceptive use remains largely borne by women. This study highlights that increasing male participation in the family planning program requires policy approaches that are not only technical-medical but also sensitive to social gender constructions.